Negative Circumstances in the Investigation of Crime. Their Conceptual Apparatus, Establishment and Use in the Interests of the Investigation - KEMPIROVA, Zhanar Seilovna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
This article addresses the use of negative circumstances in investigations. Negative circumstances as a category of forensic science have been widely studied in the papers by renowned forensic scientists. Nevertheless, the wealth of works on this subject does not allow a coherent scientific doctrine to be developed. Researchers’ opinions on the essence, notion, classification of negative circumstances and their use in the investigation proceedings can vary rather significantly. In this work, the author discusses the potential practical application of negative circumstances by the authorized officers in their crime investigation activity. The interrelationship and the interdependence of negative circumstances have been studied. The objective of this study is to provide a system-based review of the phenomenon of negative circumstances, to identify and to examine possibilities for using negative circumstances in the interests of the investigation of crime. This objective has been achieved by solving the tasks aimed at clarifying the essence of negative circumstances and their place among the other circumstances of the accident, identifying and studying the features and characteristics of negative circumstances, and optimizing the conceptual apparatus. The features and characteristics of negative circumstances, their types, and factors contributing to negative circumstances have been studied. From the author’s point of view, negative circumstances are presented as an information element of the accident under investigation which can and should be used, if any, in the activity of the subjects of investigation. The author has set forth a number of suggestions concerning further improvement of the existing criminal procedural legislation. The problems connected with identification, establishment and use of negative circumstances are considered from the practical perspective of the crime investigation activity.